Infant sleep problems: Natural history and predictors - Wake, M; Hiscock, H; Canterford, L (My University, 2007)
Wave 1 of 'Growing Up in Australia, the Longitudinal Study of Australian Children' (LSAC) showed that moderate to severe infant sleep problems were experienced in 17% of families and were associated with poorer physical health by parents, increased risk of poor mental health for mothers, and behaviour problems in preschool children. Using wave 2 data, the authors examined the rates of persistent, resolving, incident, or no sleep problems, of infants now aged 2-3 years old, as well as infant and parental predictors of incident sleep problems, and the relative contribution of parenting style and parental mental health to persistent sleep problems. This presentation features slides outlining the aims, methodology, and results of the study, which found a maternal hostile parenting style, child special health care needs, and financial stress were significant predictors of persistent sleep problems.
Keywords: Child Development -- Sleep; Child Development; Childhood and child development; Child Development; Sleep; Childhood and child development